Development of Green Chemistry-Based Practicum Guide Towards Generic Science Skills - Muhammad A. Gifary; Siti Nuryanti; Kasmudin Mustapa (Universitas Tadulako, 2024)
The research on the development of a green chemistry-based practicum guide for generic science skills aimed to measure the validity, practicality, and effectiveness. The research used is Research and Development (R&D) based on the ADDIE development model. The subjects of this study were students of class XI IPA SMAS Alkhairaat Kalukubula who had been taught the subject of the polarity of electrolyte and non-electrolyte solutions. The instruments used in this study were validation sheets, questionnaires, and an essay test. Data were analyzed by using quantitative descriptive techniques. The results showed that the practicum guide was valid for the material aspect (84%) and the media aspect (82%). The practicum guide was rated in the practical category with a score of 86%. The effectiveness of practicum guides on generic science skills, with a Cohen effect size of 1.75 in the very large effect category and student responses at 89% in the very effective category. Based on these results, the green chemistry-based practicum guide is worthy of use.